Responses and feedbacks of coupled biogeochemical cycles to climate change: Examples from terrestrial ecosystems - Finzi, Adrien C. (2011)
The biogeochemical cycles of carbon (C), nitrogen (N), and phosphorus (P) are fundamental to life on Earth. Because organisms require these elements in strict proportions, the cycles of C, N, and P are coupled at molecular to global scales through their effects on the biochemical reactions controlling primary production, respiration, and decomposition. The coupling of the C, N, and P cycles constrains organismal responses to climatic and atmospheric change, suggesting that present-day estimates of climate warming through the year 2100 are conservative. N and P supplies constrain C uptake in the terrestrial biosphere, yet these constraints are often not incorporated into global-scale analyses of Earth's climate. The inclusion of coupled biogeochemical cycles is critical to the development of next-generation, global-scale climate models.